Language Performativity - Marciniak, Magdalena (Hybris, 2011)
Austin, proposing the theory of speech acts in 1955, wanted to restrict his analyses to everyday use of language, to how it actually operates in a heterogeneous space of communication. Derrida attacked those elements of the theory of speech acts, which guided Austin’s argumentation. Among these elements were the issue of a fixed source of expression associated with the subject’s intentionality, closure of the message by the context that can be precisely defined, exclusion by Austin citations as an example of parasitic use of language. Arguments proposed by Derrida forced the defenders of speech acts theory to rethink its basic assumptions. Exchange of arguments between deconstruction and theory of speech acts dominated the sphere of research on linguistic performances. To better understand the nature of this dispute, I will present and comment two key texts: “How to do things with words?” (Austin) and “Signature Event Context” (Derrida).